2019
DOI: 10.3390/cancers11081058
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal Role of AKT2 during Dynamic Phenotypic Change of Breast Cancer Stem Cells

Abstract: Therapeutic resistance seen in aggressive forms of breast cancer remains challenging for current treatments. More than half of the patients suffer from a disease relapse, most of them with distant metastases. Cancer maintenance, resistance to therapy, and metastatic disease seem to be sustained by the presence of cancer stem cells (CSC) within a tumor. The difficulty in targeting this subpopulation derives from their dynamic interconversion process, where CSC can differentiate to non-CSC, which in turn de-diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 46 publications
0
46
0
Order By: Relevance
“…Among these three, AKT2 is much more closely associated with cancer cell metabolism, proliferation, cell survival, metastasis, angiogenesis and drug resistance [6]. In breast cancer, inhibition of AKT2 can not only effectively prevent the transformation of mesenchymal non-cancer stem cells (non-CSC) into epithelial cells but also reduce the invasive and colony formation abilities of non-CSC and CSC [7]. In colon cancer, the expression of AKT2 can affect the DNA repair ability and radiosensitivity [8].…”
Section: Introductionmentioning
confidence: 99%
“…Among these three, AKT2 is much more closely associated with cancer cell metabolism, proliferation, cell survival, metastasis, angiogenesis and drug resistance [6]. In breast cancer, inhibition of AKT2 can not only effectively prevent the transformation of mesenchymal non-cancer stem cells (non-CSC) into epithelial cells but also reduce the invasive and colony formation abilities of non-CSC and CSC [7]. In colon cancer, the expression of AKT2 can affect the DNA repair ability and radiosensitivity [8].…”
Section: Introductionmentioning
confidence: 99%
“…Knockdown of AKT2 prevented cell proliferation and stimulated apoptosis in CC cells [43]. A recent study showed that AKT2 inhibition is potential for anti-cancer therapies for its function in EMT reversion, metastasis reduction and tumor recurrence prevention [44]. To sum up, AKT2 silencing is possible to prevent CC development.…”
Section: Discussionmentioning
confidence: 99%
“…The knockdown of AKT2 prevented cell proliferation and stimulated apoptosis in CC cells [ 45 ]. A recent study showed that AKT2 inhibition has the potential for anticancer therapies for its function in EMT reversion, metastasis reduction, and tumor recurrence prevention in breast cancer [ 46 ]. To sum up, AKT2 silencing is possible to prevent CC development.…”
Section: Discussionmentioning
confidence: 99%